Genetics and pathophysiology of low-renin arterial hypertension - A. L. Markel (Вавиловский журнал генетики и селекции, 2019)
The review is devoted to the consideration of genetic determination and pathophysiology of one of the forms of hypertensive disease known as low-renin hypertension. At frst glance, the development of low-renin hypertension is “unnatural”, as renin, as a key enzyme of the renin-angiotensin system, which plays an important role in the development of hypertensive disease, is suppressed in low-renin hypertension. At the same time, the most important drugs actual in the treatment of hypertensive disease belong to the renin-angiotensin system blockers. This contradiction was resolved by a study of genetic and pathophysiological mechanisms of hypertension in some groups of patients with characteristic symptoms bringing these people together. Genetic studies of some recent decades using both family analysis and modern molecular genetic technologies have revealed the main mechanisms underlying low-renin hypertension, which can be classifed as certain syndromes with well-defned genetic and clinical features. These syndromes include cases of sporadically occurring somatic mutations in the cells of the adrenal cortex, which begin to produce aldosterone in increased amounts. Also, several oligogenic forms of low-renin hypertension were studied, some of which are associated with the hyperproduction of aldosterone, but in the others the development of low-renin hypertension was associated with mutations of genes involved in regulation of the functioning of the kidney ion channels. The discovery of some types of arterial hypertension with known mechanisms of their development is of paramount importance for medicine, as it allows for targeted efective therapy and in some cases for achieving a complete cure. However, the main contingent of patients with low-renin hypertension belongs to cases with unexplained etiology, as their development is associated with polygenic systems and with a signifcant inﬂuence of numerous environmental factors. The study of genetic and physiological mechanisms of various forms of low-renin arterial hypertension provides a good example of how penetration into the intimate mechanisms of the blood pressure regulation in each personal case makes it possible to identify some specifc syndromes and establish its fnal causes. It seems that progress in understanding the causes and mechanisms of essential hypertension lies along this way.